Taxi driver [videorecording (DVD)] - Scorsese, Martin; De Niro, Robert; Foster, Jodie; Brooks, Albert, 1947- (Sony Pictures Home Entertainment, 2007)
A psychotic taxi driver tries to save a child prostitute and becomes infatuated with a political campaigner. He goes on a violent rampage when his dreams don't work out.